PENGERUH KUALITAS PRODUK, HARGA, PROMOSI, DAN TEMPAT TERHADAP KEPUTUSAN PEMBELIAN PRODUK AIR MINUM MEREK DC PADA PT. AIR KRISTAL LESTARI DI SAMARINDA - Rada, Ikbal - (EKONOMIA, 2018)
ABSTRACTÂ The purpose of this research is, a) To know the quality of product, have positive and significant effect on buying decision of drinking water of DC brand. b) To know the price has a positive and significant effect on the buying decision of DC brand drinking water. c) To know the price has a positive and significant effect on buying decision of drinking water of DC brand. d) To know where the positive and significant impacts of DC brand drinking water purchasing decisions.The basic marketing management theory that focuses on product quality, price, promotion, place, and purchasing decisions. This research use accidental sampling method with research sample amounting to 30 people from consumer population at PT. Kristal Lestari in Samarinda. The method of analysis used is multiple linear regression. The result of the research shows that the regression equation is Y = 7.056 + 0.383 X1 + 0.162 X2 + 0.630 X3 + 0.190 X4 + e. The results showed that the promotion has the greatest influence compared with other independent variables on the purchase decision. The results of this study indicate that product quality variables have a positive and significant effect on purchasing decisions. price variables have a positive and significant effect on purchasing decisions. Promotion variables have a positive and significant impact on purchasing decisions, and place variables have a positive and significant impact on purchasing decisions.